Attention Deficit Hyperactivity Disorder (ADHD): Forensic Issues - Ian Freckelton (Bond Law Review)
ADHD has long been recognised as disproportionately present in both juvenile and adult prison populations. This is so for a number of reasons, including the potential for persons with ADHD to be disinhibited, impulsive, impaired in executive functioning and chaotic in their lifestyle. A major challenge exists, though, to assist courts to understand better how ADHD may have played a role in criminal offending and thus to be relevant to evaluations of criminal culpability or even responsibility. Another issue that arises for expert assessment is how ADHD may make the experience of custodial detention especially burdensome and be relevant in this respect also for sentencing. This article considers the overall forensic context of ADHD in criminal litigation and reviews a selection of illustrative decisions from Canada, Australia, New Zealand and the United Kingdom to identify principles on the basis of which courts can make nuanced decisions that are suitably informed by expert mental health evidence about the forensic ramifications of ADHD.